Ecofriendly oxidation of benzyl alcohol to benzaldehyde using Zr-Ni/Natural phosphate as an efficient and recyclable heterogeneous catalyst. (2020) - Laasri, Laila; El Makhfi, Mariem; Sebti, Saïd
Abstract: The partial oxidation of benzyl alcohol to benzaldehyde is a fundamental synthetic transformation in organic chemistry. However, the conventional oxidation methods pose many environmental problems such as the use of inorganic oxidants (chromates, permanganate and chlorinated oxidants) with high toxicity in organic media and the generation of a large amount of waste. In this work, we report a green approach for the oxidation of benzyl alcohol to benzaldehyde using bimetallic zirconium-nickel loaded on natural phosphate as heterogeneous catalyst with aqueous hydrogen peroxide as green oxidant under solvent-free conditions. The catalyst has been prepared by using a wet impregnation method and characterized by powder XRD and FT-IR studies. Compared to other works in literature, the developed catalyst showed relatively short reaction time (45 min), good yield (93%) and high recyclability without a significant loss in its activity.